Noradrenergic Modulation of Fear Conditioning and Extinction - Giustino, Thomas F.; Maren, Stephen (Frontiers in Behavioral Neuroscience, 2018)
The locus coeruleus norepinephrine (LC-NE) system plays a broad role in learning and memory. Here we begin with an overview of the LC-NE system. We then consider how both direct and indirect manipulations of the LC-NE system affect cued and contextual aversive learning and memory. We propose that NE dynamically modulates Pavlovian conditioning and extinction, either promoting or impairing learning aversive processes under different levels of behavioral arousal. We suggest that under high levels of stress (e.g., during/soon after fear conditioning) the LC promotes cued fear learning by enhancing amygdala function while simultaneously blunting prefrontal function. Under low levels of arousal, the LC promotes PFC function to promote downstream inhibition of the amygdala and foster the extinction of cued fear. Thus, LC-NE action on the mPFC might be described by an inverted-U function such that it can either enhance or hinder learning depending on arousal states. In addition, LC-NE seems to be particularly important for the acquisition, consolidation, and extinction of contextual fear memories. This may be due to dense adrenoceptor expression in the hippocampus which encodes contextual information, and the ability of NE to regulate long-term potentiation. Moreover, recent work reveals that the diversity of LC-NE functions in aversive learning and memory are mediated by functionally heterogeneous populations of LC neurons that are defined by their projection targets. Hence, LC-NE function in learning and memory is determined by projection-specific neuromodulation that accompanies various states of behavioral arousal.